Bibliometric and visual analysis of nocturnal enuresis from 1982 to 2022 - Li, Wenjie; Yang, Guang; Tian, Wenxiu; Li, Yunqi; Zhang, Lei; Wang, Youjie; Hong, Yanlong (Frontiers in Pediatrics, 2022)
Nocturnal enuresis is a common disorder among children that seriously affects physical and mental health and has become a social problem. Bibliometric analysis is a valid way to examine existing research results, current research hotspots and research frontiers. Current studies on nocturnal enuresis are numerous and complex, but a bibliometric analysis of the existing research on nocturnal enuresis has yet to be published. To better identify the research trends and frontiers in nocturnal enuresis, it is necessary to conduct a comprehensive review and analysis. We used bibliometric and visualization methods to analyze the 1111 papers published between 1982 and 2022 from the Web of Science core collection. Basic information about the country, institution, and authors was analyzed, which led to a basic understanding of nocturnal enuresis. The United States is the most prolific country, Ghent University is the most influential institution, and Rittig Soren is the most prominent scholar. The frequency of keywords, clustering, and the cited literature were analyzed to understand the hotspots and frontiers of research, and a brief review of the highly cited literature was conducted. The current research hotspots are the treatment modalities for nocturnal enuresis, epidemiological investigations, and the exploration of pathogenesis. Clinical research, adenoidectomy, aquaporin 2, and response inhibition are potential research hotspots. The standardization of terminology in nocturnal enuresis and the pathologies of polyuria and sleep disorder are at the forefront of research. In summary, the results of our bibliometric analysis reveal views on the current situation and the trend of nocturnal enuresis research for the first time. This study may provide guidance for promoting research on nocturnal enuresis.